2020
DOI: 10.1186/s12957-020-01905-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential risks in sentinel lymph node biopsy for cervical cancer: a single-institution pilot study

Abstract: Background: Sentinel lymph node (SLN) biopsy is an attractive technique that is widely performed in many oncological surgeries. However, the potential risks in SLN biopsy for cervical cancer remains largely unclear. Methods: Seventy-five patients with histologically confirmed cervical cancer were enrolled between May 2014 and June 2016. SLN biopsies were performed followed by pelvic lymphadenectomies and all resected nodes were labeled according to their anatomic areas. Only bilateral detections of SLNs were c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Consequently, understanding the pattern of LNM contributed to performing lymph node related surgery. In a study of 75 cervical cancer patients, obturator site was the most common area for positive SLNs (Tu et al 2020 ). However, another research showed that 44% positive SLNs were detected in external iliac area (Diaz et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, understanding the pattern of LNM contributed to performing lymph node related surgery. In a study of 75 cervical cancer patients, obturator site was the most common area for positive SLNs (Tu et al 2020 ). However, another research showed that 44% positive SLNs were detected in external iliac area (Diaz et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…A single-institution study of 75 patients with cervical cancer who underwent SLN biopsy followed by pelvic lymphadenectomy found that lymphovascular invasion significantly reduced the success rate of patient detection ( 7 ), with higher inaccuracy in detection (90.9% with lymphatic vascular invasion vs. 41.5% without, P < 0.001) and significantly higher lymph node metastasis rate (40.9 vs. 3.8%, P < 0.001). It was concluded that, in cervical cancer, the lymphatic vascular invasion has a great impact on the success rate of SLN detection ( 7 ).…”
Section: Introduction To Sentinel Lymph Node Techniquesmentioning
confidence: 99%
“…Sentinel lymph nodes refer to the first group of lymph nodes that drain the primary tumor lymph, which is the first area involved when the tumor metastasis occurs, reflecting the state of lymph node involvement in the entire region (6)(7)(8). SLN mapping is used to determine whether the tumor has developed lymphatic metastases.…”
Section: Definition Of Sentinel Lymph Nodesmentioning
confidence: 99%